Materials Selection for Eco-Aware Lightweight Friction Material - Mustafa, Ashafi'e; Abdollah, Mohd Fadzli bin; Ismail, Nurhidayah; Amiruddin, Hilmi (2014)
In the automotive industry, non-asbestos based components, such as brake pads, have been in high demand due to environmental and human health concerns. Therefore, the purpose of this study is to select an alternative friction material, which is eco-aware lightweight, cost effective, and non-toxic. This will be accomplished using Cambridge Engineering Selector (CES) Edupack software, embedded within an Eco-Audit Tool. For verification, a comparative study using the Pugh method was also investigated. The results show that Kenaf, which is a commodity plant in Malaysia, is the most suitable alternative friction material that passes all of the design stages and consumes less energy, compared to asbestos and other potential materials.